AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DI DESA ALASMALANG KECAMATAN PANARUKAN KABUPATEN SITUBONDO - Eddy Basuki; Hasan Muchtar Fauzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2018)
This study raises the issue of Accountability for Management of Village Fund Allocation in Alasmalang Village, Panarukan Subdistrict, Situbondo Regency in 2019; Based on Law Number 32 Year 2004 article 1 point 5, Regional Autonomy is the right, authority, and obligation of autonomous regions to regulate and manage their own government affairs and the interests of the local community in accordance with the laws and regulations. In this case the government provides rights, authority and obligations to each region to be able to manage what is owned by the area to achieve public welfare. The government then issued Government Regulation of the Republic of Indonesia Number 43 of 2014 concerning Implementation Regulation of Law Number 6 Year 2014 concerning villages. Local governments have broader authority in managing their regions. One form of government concern for rural area development is that the government allocates Village Funds in the state budget for income and expenditure every year for villages that are transferred through the district / city regional income and expenditure budget for rural area development, namely in the form of Village Fund Allocation ( ADD). In this study, conducted in Situbondo Regency, Panarukan Subdistrict, Alasmalang Village, was based on the lack of potential natural resources, low levels of education, knowledge and skills, limited facilities and infrastructure which could disrupt social and economic development activities. The researcher was interested in exploring the application of the principles of participation and transparency starting from planning, implementing and evaluating the accountability of village fund allocation